A comparative assessment study of the costs and benefits of eco-friendly technologies for LNG fuelled ships - Pang, Jia Min (2016)
LNG has become a future trend as a marine fuel. It is attractive in terms of low cost of LNG fuel as well as a clean fuel. This study presents the current LNG market and discusses its future potential. As the control of emissions in the sea has become a rising global concern, sailing container vessels have to follow strict environmental regulations to minimize sea pollution. Currently, there are several technologies available for LNG-fuelled ships to counter this issue. Hence, a comparative model is presented to compare the cost and benefits of LNG system and assess against with other alternative technologies such as Scrubbers and Waste Heat Recovery system. This project also extends the fuel price scenario to four scenarios to provide a different picture of the shipping market and describe the likely outcomes on the technology uptake in the maritime industry. Cash flow, net present values and payback time models are tabulated over the next 20 years to analyze the profitability and reliability of the technology variants. Results from this research study revealed that LNG system has greater and direct benefits for small-sized (2500 TEU) vessels at all ECA exposures. For medium (8500 TEU) and large-sized (18000 TEU) vessels, Scrubber dominates when ECA is lower. While at high ECA of more than 70%, both LNG system and Scrubber are profitable to use. This study thus aims to help ship owners or potential investors to make rational decisions on the application of technology and the worthiness of their investment funds.